Factors leading to the high frequency of western North Pacific tropical cyclones in late autumn 2024 - Fang-Ching Chien; Yen-Chao Chiu (Geoscience Letters)
Abstract This study examines the factors contributing to the anomalous typhoon activity observed in the western North Pacific (WNP) during late autumn 2024 (22 October–20 November, referred to as LA24). Climatological analysis reveals that the tropical cyclone (TC) activity of six typhoons during LA24 exhibited significant anomalies on both interannual and intraseasonal timescales, with the frequency and the accumulated cyclone energy (ACE) reaching 1.7 and 2.1 times the climatological mean, respectively. Spatially, LA24 TCs displayed a pronounced clustering pattern, with all systems forming at similar latitudes east of the Philippines. On the intraseasonal scale, LA24 TC activity did not follow the expected seasonal decline but instead showed a remarkable increase. LA24 was characterized by widespread positive sea surface temperature anomalies over the WNP, accompanied by higher than average relative humidity. However, although favorable, these thermodynamic conditions were not the primary drivers of the TC outbreak in LA24; instead, intraseasonal dynamical changes played that role. A northern high, primarily driven by the westward-extending WNP subtropical high, was not only abnormally strong south of Japan during autumn 2024 but also intensified rapidly during LA24. Unlike the climatological southward migration of the high, this anomaly remained at a higher latitude, leading to a significant strengthening of easterly winds north of the monsoon trough. These enhanced easterlies provided a well-defined and consistent steering flow for TC formation and movement within the monsoon trough while also amplifying positive vorticity through dynamical mechanisms, creating favorable conditions for TC activity.